Water Use Efficiency and Physiological Adaptation of Maize (Zea Mays L.) Under Drought Stress in Dryland Ecosystems - Raodatul Putri; M. Taufik Fauzi; A.A. Ketut Sudharmawan (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Drought control on dry land is one of the main factors that reduce the productivity of corn plants (Zea mays L.) due to disruption of physiological processes and plant metabolism. This study aims to analyze the relationship between water use efficiency (WUE) and the physiological adaptation of corn plants to water deficit conditions through a literature review approach. The study was conducted using various national and international scientific articles published in the 2022–2025 period. The results of the study showed that drought stress caused a decrease in the rate of photosynthesis, leaf water content, and plant biomass formation due to stomata closure and increased accumulation of reactive oxygen species (ROS). Drought-tolerant corn plants have the ability to maintain water use efficiency through stomata regulation, proline accumulation, increased antioxidant activity, and the development of a more adaptive root system. In addition, the application of precision irrigation technology and adaptive agronomic management can improve water use efficiency and support crop productivity on dry land. Thus, the integration of physiological adaptation and adaptive cultivation strategies is an important approach in supporting the sustainability of maize production under climate change conditions.